PRODUCTIVE HOUSING: DOMESTIC SPACE AND PRODUCTIVE SPACE WITH PASSIVE SOLAR ENERGY UTILIZATION - Adinda Sih P. R. Utami; Happy Ratna Santosa; I Gusti Ngurah Antaryama (Journal of Architecture&ENVIRONMENT, 2012)
Productive housing is an alternative being done for increasing family’s economy. The existence of productive housing was caused some conflicts, one of them is the space conflict. Space conflict was due to overlapping between domestic needs and economy needs. This happens also in the research area, Kampung Sukolilo, which is famous with processed fisheries product. Space conflicts did not only occur in the house, but also occured at the surrounding. Conflict occurred due to the needs of economic space that was always increasing while the house was not able to accom-modate for more. In addition, public space conflict also occured due to production process, the drying of fisheries products, which rely heavily on solar heat. This research is expected to observe the form of adaptability in utilizing passive solar energy in housing that could minimize public area conflict. To achieve the object-tives of this study, there are several steps that have been overcome include identi-fying the factors causing space conflicts and how much space conflicts that occu-red. Identification was conducted by interviews and field observations. From the research, it was found that the people in Kampung Sukolilo has done several innovations in their house and surrounding. The house orientation in Kampung Sukolilo is to north and south actually very beneficial for drying process. It is because the house will cast the shadow to other house not to cast shadow on the alley or drying area. The passive solar is applied in the house for reduce the humidity and for drying process.